Odpowiedź :
Odpowiedź:
[tex]a)\\\\2(x+3)=10\\\\2x+6=10\\\\2x=10-6\\\\2x=4\ \ /:2\\\\x=2\\\\\\e)\\\\3(x+3)=2(x+4)+x+1\\\\3x+9=2x+8+x+1\\\\3x+9=3x+9\\\\3x-3x=9-9\\\\0=0\\\\R\'ownanie\ \ to\.zsamo\'sciowe\ \ ma\ \ niesko\'nczenie\ \ wiele\ \ rozwiaza\'n\\\\\\b)\\\\3(x-1)+2=8\\\\3x-3+2=8\\\\3x-1=8\\\\3x=8+1\\\\3x=9\ \ /:3\\\\x=3[/tex]
[tex]c)\\\\2(13-x)-9=1\\\\26-2x-9=1\\\\17-2x=1\\\\-2x=1-17\\\\-2x=-16\ \ /:(-2)\\\\x=8\\\\\\d)\\\\3(1-x)+2=-7\\\\3-3x+2=-7\\\\5-3x=-7\\\\-3x=-7-5\\\\-3x=-12\ \ /:(-3)\\\\x=4[/tex]
[tex]f)\\\\4(3x+2)+5(2x+3)=-(2x+13)\\\\12x+8+10x+15=-2x-13\\\\22x+23=-2x-13\\\\22x+2x=-13-23\\\\24x=-36\ \ /:24\\\\x=-\frac{36}{24}\\\\x=-\frac{3}{2}\\\\x=-1\frac{1}{2}\\\\\\g)\\\\4(x-2)-2(x-4)=5(x+1)-3x\\\\4x-8-2x+8=5x+5-3x\\\\2x=2x+5\\\\2x-2x=5\\\\0=5\\\\R\'ownanie\ \ sprzeczne\ \ nie\ \ ma\ \ rozwiazania[/tex]
[tex]h)\\\\2(x-4)=2(2x-1)+6(x+1)\\\\2x-8=4x-2+6x+6\\\\2x-8=10x+4\\\\2x-10x=4+8\\\\-8x=12\ \ /:(-8)\\\\x=-\frac{12}{8}\\\\x=-\frac{3}{2}\\\\x=-1\frac{1}{2}[/tex]